2020
DOI: 10.1002/cne.24889
|View full text |Cite
|
Sign up to set email alerts
|

Neural coding of action in three dimensions: Task‐ and time‐invariant reference frames for visuospatial and motor‐related activity in parietal area V6A

Abstract: Goal-directed movements involve a series of neural computations that compare the sensory representations of goal location and effector position, and transform these into motor commands. Neurons in posterior parietal cortex (PPC) control several effectors (e.g., eye, hand, foot) and encode goal location in a variety of spatial coordinate systems, including those anchored to gaze direction, and to the positions of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…Similar results were recently found in V6A using a decoding analysis; the authors reported an evolution of visuo-to-motor coding during the execution of reaching and grasping (Filippini et al, 2017(Filippini et al, ,2018. Moreover, the stability of the correlations found in most epochs is reminiscent of the stability of a mixed body/hand reference frame found in V6A (Hadjidimitrakis et al, 2020;Piserchia et al, 2017). Dynamic processing in PPC is controversial with some works reporting stationary or not-stationary encoding of information (Astrand et al, 2015;Crowe et al, 2010;Meyers et al, 2008).…”
Section: A Dynamic Representation Of Visuospatial Informationsupporting
confidence: 78%
“…Similar results were recently found in V6A using a decoding analysis; the authors reported an evolution of visuo-to-motor coding during the execution of reaching and grasping (Filippini et al, 2017(Filippini et al, ,2018. Moreover, the stability of the correlations found in most epochs is reminiscent of the stability of a mixed body/hand reference frame found in V6A (Hadjidimitrakis et al, 2020;Piserchia et al, 2017). Dynamic processing in PPC is controversial with some works reporting stationary or not-stationary encoding of information (Astrand et al, 2015;Crowe et al, 2010;Meyers et al, 2008).…”
Section: A Dynamic Representation Of Visuospatial Informationsupporting
confidence: 78%
“…This suggests that hV6A encodes the target of reaching in both retinotopic (farther than the gaze) and spatial (far from the body) frames of references. Alternatively, it could be that hV6A is involved in the remapping of visual target information from a retinotopic to a hand-centered reference frame, a process that may occur during the reaction time, as also suggested by a recent paper (Hadjidimitrakis et al 2020). All these views are well in agreement with the presence in monkey V6A of neurons with visual receptive fields in retinal, spatial, and in mixed retinal-spatial coordinates (Galletti et al 1993(Galletti et al , 1995Marzocchi et al 2008;Bosco et al 2016) (Bosco et al 2015) (Hadjidimitrakis et al 2020).…”
Section: Effect Of Tms On Peripheral and Foveal Reachingsupporting
confidence: 70%
“…The available evidence strongly indicates that the monkey parietal area PEc plays a crucial role in the integration of signals defining the location of the goal in terms of distance (Hadjidimitrakis et al 2015) for locomotor action planning, and related to optic flow (Raffi et al 2011) for obstacles avoidance. Area PEc is a visuo-somatosensory area located in the crown of the hemispheres between area PE, which is mainly somatosensory (De Vitis et al 2019), and areas V6Ad and V6Av, which are mainly visual (Gamberini et al 2020;Hadjidimitrakis et al 2020). It exhibits a somatotopic organization that has a clear leg, in addition to arm, representation (Gamberini et al 2020).…”
Section: Multisensory Environmental Affordances For Locomotor Actionsmentioning
confidence: 99%